Preoperative diagnosis of cervical cystic lesions using magnetic resonance imaging: a retrospective study - Makiko Omi; Yumiko Oishi Tanaka; Nozomi Kurihara; Yuko Sugiyama; Akiko Tonooka; Motoko Kanno; Atsushi Fusegi; Yoichi Aoki; Sachiho Netsu; Akiko Abe; Terumi Tanigawa; Sanshiro Okamoto; et al. (BMC, 2024)
Abstract Background We conducted this study to clarify the magnetic resonance imaging (MRI) characteristics of lobular endocervical glandular hyperplasia (LEGH) and Nabothian cysts. Methods This study included 48 patients who underwent hysterectomy at our institution between 2016 and 2020 for suspected LEGH. Histopathological studies confirmed the presence of 25 Nabothian cysts and 23 cases of LEGH. We retrospectively analyzed five characteristic MRI findings: (1) located at the upper cervical canal, (2) positioned within the cervical stroma, (3) not circumscribing the cervical canal, (4) low- to iso-intensity on T1-weighted images (T1WI), and (5) "cosmos" or "microcystic" pattern. We compared the diagnostic accuracy of these findings for LEGH and Nabothian cysts using sensitivity, specificity, and predictive values. Combinations of findings were also calculated. Results The characteristics "cosmos" or "microcystic" pattern, lesion not circumscribing the cervical canal, and low/iso-intensity on T1WI had a sensitivity and specificity greater than 50%. The sensitivity was 73.9% and specificity 84.0% when a combination of "cosmos" or "microcystic" pattern and lesion not circumscribing the cervical canal was present. Conclusion The coexistence of a "cosmos" or "microcystic" pattern and not circumscribing the cervical canal was the most characteristic finding that distinguished LEGH from Nabothian cysts. When neither of these findings is present, Nabothian cyst can be suspected.